New Structures in Odd-Odd 120 - 李黎 刘弓冶 马英君 赵延新 周文平 邱远 于德阳 竺礼华 吴晓光 郝昕 刘颖 李雪琴 潘波 郑云 汪雷 李广生 (等离子体科学和技术：英文版, 2012)
t The excited states of the doubly-odd 120^Ⅰ have been investigated via the 110^Pd（14^N, 4n） and the 114^Cd（10^B, 4n） reactions at beam energies of 64 MeV and 48 MeV, re-spectively. The previously known bands are extended, and a new band structure is established. The yrast band is assigned to the πrh11/2 vh11/2 configuration instead of the previously as- signed πg7/2 vh11/2 configuration. Possible configurations of the other observed bands are also discussed.